(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article highlights the use of bentonite clays, which are one of the non-traditional agricultural ores, as fertilizers and obtaining high and high-quality crop yields, as well as a positive effect on changing the mechanical composition of the soil, which is one of the important factors in increasing soil fertility.